POWER GENERATOR FROM OCEAN WAVE ENERGY CONVERSION - Aribowo, Widi; Agung, Achmad Imam; Haryudo, Subuh Isnur; Muarif, Syamsul (Fakultas Teknik Universitas Muria Kudus, 2020)
The need for electrical energy has increased every year. On the other hand, the largest power plants in Indonesia still use non-renewable energy sources such as coal and petroleum, while these non-renewable energy sources will eventually run out. To anticipate running out of this energy, a renewable energy source is needed. This existence will not run out even though it is consumed every day. Renewable energy that can be used for conversion into electrical energy in coastal areas is wave power. The waves that always crash on the shoreline can be used to drive turbines. The turbine rotates due to the crashing waves connected to a DC generator. It will convert mechanical energy into electrical energy. The electrical energy generated by the DC generator is used to charge the battery. The purpose of this research is the know-how to design a wave power generator and to determine the performance. The experimental method is used in this study. In the results, the generator works optimally during the day with the resulting voltage of 10.6 V to 10.7 V with rotation speed of 623 Rpm to With 710 Rpm.